Optimized production of transgenic buffalo embryos and offspring by cytoplasmic zygote injection. Issue 1 (December 2015) - Meng, Fanli; Li, Hui; Wang, Xiaoli; Qin, Guangsheng; Oback, Björn; Shi, Deshun
Abstract Background Cytoplasmic injection of exogenous DNA into zygotes is a promising technique to generate transgenic livestock. However, it is still relatively inefficient and has not yet been demonstrated to work in buffalo. We sought to improve two key technical parameters of the procedure, namely i) how much linear DNA to inject and ii) when to inject it. For this, we introduced a constitutively expressed enhanced green fluorescent protein (EGFP) plasmid into buffalo zygotes. Results First, we found that the proportion of EGFP-expressing blastocysts derived from zygotes injected with 20 or 50 ng/μL DNA was significantly higher than from those injected with 5 μg/mL. However, 50 ng/μL exogenous DNA compromised blastocyst development compared to non-injected IVF controls. Therefore the highest net yield of EGFP-positive blastocysts was achieved at 20 ng/μL DNA. Second, zygotes injected early (7–8 h post-insemination [hpi]) developed better than those injected at mid (12–13 hpi) or late (18–19 hpi) time points. Blastocysts derived from early injections were also more frequently EGFP-positive. As a consequence, the net yield of EGFP-expressing blastocysts was more than doubled using early vs late injections (16.4 % vs 7.7 %). With respect to blastocyst quality, we found no significant difference in cell numbers of EGFP-positive blastocysts vs non-injected blastocysts. Following embryo transfer of six EGFP-positive blastocysts into four recipient animals, two viable buffalo calves were born. Biopsied ear tissues from both buffalo calves were analyzed for transgene presence and expression by Southern blot, PCR and confocal laser scanning microscopy, respectively. This confirmed that both calves were transgenic. Conclusions Our cytoplasmic injection protocol improved generation of transgenic embryos and resulted in the first transgenic buffalo calves produced by this method.